The Use of Sign Language in News Presentations for Hearing Impaired Viewers to Promote Sustainable and Inclusive Media - Atinuke Olubukade Akintayo; Chukwuemeka Samuel Ezeoye; Mobolaji Grace Akintaro; Olugbenga Charles Adewale (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2026)
Inclusive media create a platform for all audiences, including persons with disabilities especially those with hearing impairment challenge. It is against this backdrop this study investigates the use of sign language in news presentations to promote sustainable and inclusive media for the hearing impaired at Wesley School, Surulere, Lagos, Nigeria. The objectives were to: investigate the types of stations that use sign language and their impact on deaf viewers, evaluate how sign language in new presentation helps deaf viewers at Wesley school access information and suggest ways to improve the use of sign language in Nigerian news for inclusivity and overcome accessibility challenges. The study utilized a survey targeting 200 members at Wesley Schools, including students, teachers, parents, and staff who rely on Nigerian Sign Language. The sample size of 200 participants were selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using qualitative analysis to capture opinions and experiences. Findings revealed that integrating Nigerian Sign Language in news presentation significantly enhances comprehension among deaf viewers. The study also found that accessible news formats foster sustained engagement and social inclusion, with long-term benefits including increased participation in civic and community activities. The study concluded that consistent sign language used in news presentations is essential for inclusivity, recommending that Sign-interpreted news must be introduced to the curriculum of hearing-impaired schools to promote understanding and involvement in the media literacy process. It is the responsibility of regulatory institutions to agree on using sign language or sign language interpretation in televised news as a norm in inclusive communication. Television stations need to have a culture of allocating sign language interpreters whenever it comes to delivering news to its viewers regularly in order to give the deaf population a chance to access important information, particularly relating to health and government policies.